2000
DOI: 10.1097/00000372-200004000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucinous Carcinoma of the Skin

Abstract: Primary mucinous carcinomas of the skin are very rare. To date, 120 cases have been described in the literature. This tumor is a histologic subtype of sweat gland carcinoma. Because of the histopathologic appearance, primary mucinous carcinoma of the skin can be mistaken for metastasis from extracutaneous sites. We report on the cases of two elderly women with mucinous carcinomas arising in the scalp. Immunohistochemical staining of both tumors was positive for low-molecular-weight cytokeratin and epithelial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
2
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 34 publications
2
71
2
3
Order By: Relevance
“…Some of them show neuroendocrine features (Wako et al 2003). The present case lacked the immunoreactivity for CEA and GCDFP-15, but this does not rule out the possibility of mucinous carcinoma of the skin because some cases of this neoplasm showed no reactivity for CEA (Bellezza et al 2000).…”
Section: Case Reportcontrasting
confidence: 74%
See 3 more Smart Citations
“…Some of them show neuroendocrine features (Wako et al 2003). The present case lacked the immunoreactivity for CEA and GCDFP-15, but this does not rule out the possibility of mucinous carcinoma of the skin because some cases of this neoplasm showed no reactivity for CEA (Bellezza et al 2000).…”
Section: Case Reportcontrasting
confidence: 74%
“…In general, cutaneous mucinous carcinoma shows carcinoma cells arranged in cords, small nests and small tubules embedded in mucinous materials which are separated by fibrous septae (Lennox et al 1952;Mendoza and Helwig 1971;Lever and Lever 1990;Bellezza et al 2000;Breier et al 2000;Ohnishi et al 2002;Wako et al 2003). The present case, in contrast, showed that relatively large tumor nests with adenocystic appearances with pseudolumens were embedded in mucinous stroma.…”
Section: Case Reportcontrasting
confidence: 64%
See 2 more Smart Citations
“…4 Recommended treatment includes standard to wide local excision. 2,3,9,12 Other approaches include Mohs surgery, 13 the addition of regional node dissection, 4 and the use of adjuvant hormone therapy with antiestrogenic agents, such as tamoxifen, to reduce the risk of recurrence. 10 Recurrent PCMS appears to be resistant to both chemotherapy and radiation.…”
Section: Discussionmentioning
confidence: 99%